HUBUNGAN ANTARA TINGKAT PENGETAHUAN PEROKOK AKTIF TENTANG BAHAYA ROKOK DENGAN MOTIVASI BERHENTI MEROKOK PADA SISWA SMA MUHAMMADIYAH CIPONDOH - Rina puspita sari; sulaeman M.Pd; fitri angraini (Universitas Yatsi Madani, 2019)
2017, smoking habits increase in the younger generation that the prevalence of adolescents aged 15-19 smokers doubled from the previous year. One of the causes is the lack of knowledge of the teens about the danger of smoking. This study aims to determine the relationship between the level of knowledge of active smokers about the dangers of cigarette with the motivation to stop smoking at SMA Muhammadiyah Cipondoh . The method in this study using quantitative method with cross sectional design. The sample used as many as 76 people, implemented in April 2018. The instrument used is a cautionary. The result of this study there is no significant relationship between the level of knowledge of active smokers about the danger of cigarette with the motivation to stop smoking at SMA Muhammadiyah Cipondoh with P value 0,283 > α (0,05). Conclusions and suggestions of this study is that there is no significant relationship between the level of knowledge of active smokers about the dangers of cigarette with the motivation to stop smoking. therefore, it is necessary to conduct futher research on the factors that influence the motivation of active smoker to quit smoking.